2006
DOI: 10.1086/498499
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization of Radio Bursts Due to Reflection off Sharp Boundaries in the Solar Corona

Abstract: Depolarization of solar radio bursts requires reflection off boundary layers no thicker than about a wavelength (a few meters at most) between regions with large density ratios. The implied inhomogeneities suggest that the corona is much more highly and sharply structured than can be resolved from observations at other wavelengths. A simplified version of magnetoionic theory is used to derive a depolarization coefficient; the effect of the magnetic field is ignored in treating the dispersion, but taken into ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…A simplified theory of depolarization due to reflection was proposed by Melrose (2006). According to this theory, when a wave in one magnetoionic mode is reflected at a sharp boundary, waves in both modes are generated.…”
Section: Depolarization Due To Single Reflectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A simplified theory of depolarization due to reflection was proposed by Melrose (2006). According to this theory, when a wave in one magnetoionic mode is reflected at a sharp boundary, waves in both modes are generated.…”
Section: Depolarization Due To Single Reflectionmentioning
confidence: 99%
“…To calculate the depolarization coefficient, we used the model of Melrose (2006). In this model, (1) the magnetic field is ignored in the refractive indices but is taken into account in the circular polarizations; (2) the sharp boundary layer is assumed to be parallel to the magnetic field lines and to have a thickness of less than about one wavelength; and (3) the incident waves, magnetic field, and normal to the boundary are assumed to be coplanar.…”
Section: Comparison Between Model and Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since lower intrinsic polarization can occur only if the initial frequency exceeds the x-mode cutoff frequency (f x cut ), the previous expectation that LMC and nonlinear processes would produce only o-mode radiation meant that depolarization theories were mainly investigated. These include mode coupling [29], scattering by low frequency waves [30,31], and reflection at density inhomogeneities [32]. However, Mjølhus [20] showed that an incident xmode wave perpendicular to B 0 can undergo LMC into an ES wave and a reflected x-mode wave at ionospheric density irregularities.…”
Section: Introductionmentioning
confidence: 99%